Co-becoming Bawaka: Towards a relational understanding of place/space. (August 2016) - Country, Bawaka; Wright, Sarah; Suchet-Pearson, Sandie; Lloyd, Kate; Burarrwanga, Laklak; Ganambarr, Ritjilili; Ganambarr-Stubbs, Merrkiyawuy; Ganambarr, Banbapuy; Maymuru, Djawundil; Sweeney, Jill
We invite readers to dig for ganguri (yams) at and with Bawaka, an Indigenous Homeland in northern Australia, and, in doing so, consider an Indigenous-led understanding of relational space/place. We draw on the concept of gurrutu to illustrate the limits of western ontologies, open up possibilities for other ways of thinking and theorizing, and give detail and depth to the notion of space/place as emergent co-becoming. With Bawaka as lead author, we look to Country for what it can teach us about how all views of space are situated, and for the insights it offers about co-becoming in a relational world.